Evolution and crustal contamination of igneous rocks from the Palaeocene volcanic district of North-West Scotland - Nicoll, Graeme (Trinity College (Dublin, Ireland). Department of Geology, 2009)
This study was undertaken using a multidisciplinary approach employing detailed field mapping and geochemical sampling of rocks from the Isle of Rum, Ardnamurchan, Isle of Mull and the Isle of Eigg in North West Scotland. Field investigations were followed up by strontium, neodymium and lead isotope determination, complimented with major, trace and rare earth elements, for a host of igneous rock compositions ranging from basaltic to rhyolitic as well as metamorphic basement rocks. This study was undertaken in order to better understand: (i) the generation of voluminous felsic magmas, (ii) the underlying crustal structure of this part of Scotland and (iii) the temporal evolution of these large igneous centres forming on the thinned and stretched pre-rift North Atlantic Margin. Detailed new field investigations carried out on the Isle of Rum further delineate the numerous felsic igneous rocks at this centre. Rhyodacite ignimbrites are mapped out and correlations across the island are suggested. In addition, these sequences appear linked to a large vent structure discovered in the south of the island. The significance of mafic xenoliths and inclusions entrained within the Am Mam-type intrusion breccias must be considered in order to fully understand the magmatic evolution of the Rum Centre. These xenoliths characterize the earliest mafic magmas which led to large-scale crustal anatexis. The Am Mam breccia is important as it represents a rare example within the British-Irish Palaeocene Igneous Province of a lithic-rich intermediate product of intruding mafic magmas and crustal partial melts.
Keywords: Geology, Ph.D.; Ph.D. Trinity College Dublin